Treatment of Helicobacter Pylori Infections Using Moxifloxacin-Triple Therapy Compared to Standard Triple and Quadruple Therapies - Ahmed Mansur Kadhim; Mohammed, Mohammed Mahmood; Hussein Muhammad Hassan Abdul-Hussein; sultan, Yasir Sabeeh Abdulridha (Iraqi Journal of Pharmaceutical Sciences, 2023)
Helicobacter pylori (H. Pylori) is one of the most common infectious human pathogens. H. pylori could induce inflammation, that causes illnesses and disorders of upper gastrointestinal which including peptic ulcer diseases, dyspepsia, gastroesophageal reflux disease and gastric mucosa-associated lymphoid tissue (MALT) lymphoma. It is important to use a better tolerated and greatly effective eradication regimen. In this study, 75 newly diagnosed adult patients with H. pylori infection were included and completed the study, they were allocated into three groups with three different treatment regimens for H. pylori eradications; Group A (25 patients) received oral standard clarithromycin-based triple therapy for 14 days. Group B (25 patients) received oral bismuth based-quadruple therapy for 10 days. Group C (25 patients) received oral moxifloxacin-based triple therapy for 14 days. The results reported in this study indicated a significant higher eradication rate of Group B and Group C (84% and 80%, respectively) of patients with H. pylori infections compared to that of Group A (52%). The incidence of adverse effects were appeared as 72%, 64% and 24% of patients in group A, B and C respectively. The use of moxifloxacin triple regimen for H. pylori eradication, present with eradication efficacy parallel to that of quadruple regimen which were significantly higher compared to that of clarithromycin triple regimen. Also moxifloxacin triple therapy is more tolerable and does not increase the incidence of overall adverse effects compared to other regimens used in this study.